Development of Literacy Module Based on the Local Wisdom of Maja Labo Dahu Using the Teaching at the Right Level (TaRL) Approach - Tasrif Tasrif; Nurhasanah Nurhasanah (Program Studi Manajemen Pendidikan, 2024)
Literacy is the most important element in the education and learning process. Basic literacy consists of reading and writing. Student learning outcomes start from students' ability to master basic literacy. The development of literacy modules is an innovation in learning learning innovation for students in primary school. Module development literacy module development based on local wisdom with the Teaching at the Right Level (TaRL) approach is very effective to address students' needs and pedagogical approach is very effective to answer the needs and pedagogical needs of students. The purpose of the research to develop a literacy module, analyze its feasibility and effectiveness to improve literacy learning outcomes. effectiveness to improve literacy learning outcomes. This research is Research and Development (R&D) model with ADDIE (Analyze, Design, Develop, Implement and Evalutie) model. The research subjects were teachers and students grade V of SDN Nanga Na'e and SDN Radu. Data collection used questionnaires, observation sheets and interview guidelines. The results showed that; (1) the process of developing a module based on local wisdom majalabo dahu with the TaRL approach resulted in a literacy module teaching material product. TaRL approach resulted in literacy module teaching material products, (2) the product products are very feasible from the material aspect (84.4%), media aspect (91.2%), and learning aspects (89.8%). (3) the module product is effective in improving students' learning literacy. The learning outcomes of students who were treated with the module based module based on majalabo dahu local wisdom with TaRL approach is higher than without the module based on local wisdom. higher than without module based on majalabo dahu local wisdom with TaRL approach (thit = 0.05). with TaRL approach (thit = 3.756, p-value = 0.0005). Students' positive response to the module based on local wisdom majalabo dahu with TaRL approach approach that has been developed obtained student feedback of 84.8%. Conclusion This research is a module product based on majalabo dahu local wisdom with the TaRL approach developed in elementary schools. TaRL approach developed in elementary schools has gone through the appropriate development procedure, has a very feasible development procedures, has excellent feasibility, and is effective in improving students' literacy learning outcomes in elementary school.